2020
DOI: 10.1002/stem.3279
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine (m6A) RNA modification in cancer stem cells

Abstract: Cancer stem cells (CSCs), a unique subset of undifferentiated cells with stem cell-like properties, have emerged as driving forces in mediating tumor growth, metastasis, and therapeutic resistance. Recent advances have highlighted that N6-methyladenosine (m6A) RNA modification plays an important role in cancer biology and CSCs. Dynamic m6A decoration has been demonstrated to be involved in CSC generation and maintenance, governing cancer progression and therapeutic resistance. In this review, we provide the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 71 publications
(218 reference statements)
0
56
0
Order By: Relevance
“…As a current highly promising RNA modification, m6A methylation has been experimentally confirmed to play a key role in the development of various cancers ( Vu et al, 2017 ), while the study of m6A methylation provides a new perspective for GBM treatment. m6A modifications have been shown to potentially affect the formation of a variety of peripheral tumor microenvironments (TME), be involved in cancer stem cells (CSCs) generation and maintenance, the control of cancer progression, and treatment resistance ( Ma and Ji, 2020 ). Previous studies have confirmed that GBM is more heterogeneous than other peripheral tumors, suggesting that multiple factors may influence developmental plasticity and immune checkpoint blockade therapy in GBM, possibly including the TME, RNA modifications, and stem cell phenotype ( Malta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a current highly promising RNA modification, m6A methylation has been experimentally confirmed to play a key role in the development of various cancers ( Vu et al, 2017 ), while the study of m6A methylation provides a new perspective for GBM treatment. m6A modifications have been shown to potentially affect the formation of a variety of peripheral tumor microenvironments (TME), be involved in cancer stem cells (CSCs) generation and maintenance, the control of cancer progression, and treatment resistance ( Ma and Ji, 2020 ). Previous studies have confirmed that GBM is more heterogeneous than other peripheral tumors, suggesting that multiple factors may influence developmental plasticity and immune checkpoint blockade therapy in GBM, possibly including the TME, RNA modifications, and stem cell phenotype ( Malta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LLPS is involved in modulating RNA N6 methyladenosine (m6A) (Yu et al, 2019), which had been found to have a key role in tumor occurrence and development (Chen et al, 2020;Ma and Ji, 2020). In addition, however, the role of LLPS in digestive system tumors is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LLPS could also affect transcriptional regulation, maintaining genomic stability and signal transduction, which may contribute to the occurrence and progression of tumors ( Peng et al, 2021 ). Moreover, LLPS is involved in modulating RNA N6 methyladenosine (m6A) ( Yu et al, 2019 ), which had been found to have a key role in tumor occurrence and development ( Chen et al, 2020 ; Ma and Ji, 2020 ). In addition, however, the role of LLPS in digestive system tumors is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…M6A modification is involved in all mRNA metabolic processes, including maturation, transport, splicing, translation, and degradation ( Song et al, 2020 ; Li et al, 2021b Li et al, 2021c ; Lou et al, 2021 ). M6A RNA methylation exerts critical biological functions in mammals, such as tissue development, circadian rhythms, DNA damage responses, gender identification, and tumor occurrence and development ( Xu et al, 2020a ; Li et al, 2020 ; Ma and Ji 2020 ; Gu et al, 2021b ; Wu and Wang 2021 ). In this review, we discuss the potential mechanisms of m6A methylation-related regulators in BC initiation and development.…”
Section: Introductionmentioning
confidence: 99%